Analysis of the Selection of River Transportation Modes that are Integrated with Land Transportation in the City of Banjarmasin - Muhammad Tsaqib Muallif; Sutanto Soehodho; Nahry Nahry (Pusat Publikasi Nusantara, 2024)
The city of Banjarmasin, as the center of economic growth in South Kalimantan, faces significant challenges in terms of mobility. The development of river public transportation is one of the alternatives to overcome urban transportation problems. This study has significance in providing a holistic view of the factors that need to be considered in the selection of river transportation modes that are integrated with land transportation. The study was conducted in the areas of North Alalak Village and Sungai Lulut Village. The data processing method in this study involves testing the completeness of primary and secondary data to describe field conditions, then analyzing the preferences for choosing transportation modes using the AHP method which includes steps such as defining problems, creating hierarchical structures, conducting pairs comparisons, calculating eigenvalues and testing consistency, while the data analysis stage includes the calculation of consistency ratios, consistency vector, average of entries (Zmax) and Consistency Index (CI) to determine the final preference of each alternative. The analysis of priority weights between criteria is calculated to find out the order of the most influential criteria in selecting transportation modes. The results of the study can provide guidance for decision-making at the level of governments, transport companies and communities in developing and adopting more efficient transport systems. This research is expected to be useful for the author to expand insights, for the government and operators as input in the development of integrated transportation, and for the general public as a reference for more efficient modes of transportation.